IMPACT ANALYSIS OF IMPLEMENTATION OF AUTOMATION TECHNOLOGY ON REFRIGERATOR OUT DOOR FORMING PROCESS IN ELECTRONICS COMPANY TANGERANG - Slamet Riyadi (Operations Excellence: Journal of Applied Industrial Engineering, 2018)
This research is conducted at an electronics company in Tangerang which produces a refrigerator with an average production capacity of 5,500 units per day. To improve productivity in the manufacturing process at the company has done several automation processes in several workstations that allow automation processes. Takt time reduce from 12 seconds to 8.5 seconds and the number of operators 80% decreased from 10 operators to only 2 operators. It also has the effect of reducing the possible risk of accidents for operators. Automation processes using robots have advantages in terms of process stability and ease in the adjustment of motion, making it particularly appropriate in automation processes in the manufacturing process industry. That is based on analysis conducted by using SWOT analysis method.